Tobacco smoking trends and treatment outcomes in Tuberculosis patients of district Shimla, Himachal Pradesh, India: a cohort study - Singh, Harshvardhan; Thakur, Anita; Mazta, Salig Ram; Chauhan, Tripti (International Journal Of Community Medicine And Public Health, 2017)
Background: India carries the highest burden of tuberculosis worldwide. To achieve the goals of the ‘END TB’ strategy, it is imperative to understand the factors which can influence the treatment outcomes. The objectives were to study the socio-demographic characteristics of the subjects and to study the factors influencing treatment outcomes in the TB patients. Methods: A prospective cohort study design was employed and all patients (n=117) who were registered for category I DOTS during the last quarter of 2015 were included after obtaining written informed consent. Home visits with patient interviews were conducted to collect information on determinants. Univariate and binary logistic regression models were employed. Results: The overall treatment success rate was 93.2% (Cure rate=87%, treatment completion rate=100%). Default, death, failure and lost to follow up rates were 2.6%, 2.6%, 0.8% and 0.8% respectively. Those with a history of tobacco smoking [RR: 6 (1.27-28.37); p=0.02], second hand smoke [RR: 8.75 (1.11-68.88); p=0.02], indoor air pollution [RR: 7.89 (1.10-62.13); p=0.02] and alcohol use [RR: 6.13 (1.57-23.93); p=0.01] had higher risks of developing unfavourable treatment outcomes. The commonest cause of indoor air pollution was smoke surfacing out of fire-wood used for cooking and tobacco. Conclusions: The treatment success rates conform to the END TB strategy targets of 90%. Tobacco smoking, second hand smoke, indoor air pollution and alcohol intake were associated with adverse outcomes. Health education regarding the ill effects of tobacco and alcohol with regards to the disease preventability and curability needs to be further intensified. Larger studies to determine the effect of indoor air pollution as a risk factor and its impact on treatment outcomes by contemporary scientific methods by collaborating with other agencies involved in environmental studies is highly recommended.